A Study on Chiang Kai-shek’s Christian Faith in Ningbo, 1949 - WU, Lingyun (Journal of Research for Christianity in China (JRCC), 2025)
Chiang Kai-shek (1887–1975), a native of Ningbo, Zhejiang, was both President of the Republic of China during the Chinese Civil War and a professing Christian. This article investigates the expression of Chiang’s Christian faith in 1949 by examining his participation in a range of religious activities while in Ningbo. Methodologically, the study combines historical analysis of primary sources with a sociological perspective on religion, enabling a nuanced interpretation of Chiang’s religious practices within their broader cultural and political contexts. The analysis demonstrates that Chiang’s Christianity was not an isolated religious identity but one deeply intertwined with Confucian ethical traditions and marked by enduring Buddhist influences. Moreover, as a political leader, Chiang’s choices concerning ancestral rites and other religious observances reveal the tension between personal belief, family traditions, and the exigencies of socio-political life. This case thus illuminates the complex interplay of faith, culture, and political authority in modern Chinese history.